The relationship of transference between the analyst and theories (Psicologia USP, 2013)
This paper explores the relationship of transference between the analyst and theories, examining its narcissistic, non-narcissistic and oedipal aspects, as proposed by Caper (1999). The narcissistic aspects of transference refer to the analysts ability to project his internal objects on the theory; the non-narcissistic aspects refer to his ability to perceive the theory as an object that is independent from his projections; the oedipal aspects refer to the analysts ability to project his internal objects on the theory and to perceive it as something apart from oneself, maintaining the paradox. To view the theory as separate from oneself is to accept that it establishes relationships with other objects, from which the analyst is excluded; this acceptance, by its turn, allows the analyst to establish relationships with new objects, from which the theory is excluded. The necessary emotional distance between analyst and theory is thus given by the analysts living connection to his patients.